ARTISTIC AND AESTHETIC COMPETENCIES DEVELOPMENT: TRAINING TEACHERS USING DECORATIVE AND APPLIED ARTS - Marushchak, Oksana; Zuziak, Tetiana; Savchuk, Iryna; Rohotchenko, Oleksii (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
As Ukrainian national system of education is coming into being, aiming to promote development of personal competences on the basis of culture, art, and folk traditions of the Ukrainian people, introducing the spiritual heritage to the young generation, the problem of developing artistic and aesthetic competencies of the future teachers by means of decorative and applied arts becomes topical. The didactic value of the arts, as well as their limitless potential for competencies development are well recognized. This urged us to develop an artistic and aesthetic competencies training technique for the future teachers with the use of decorative and applied arts. The aim of the study is to test experimentally the effectiveness of this technique. The theoretical methods used are: analysis of psychological, pedagogical, methodological and specialized publications, of educational documentation; analysis, synthesis, abstraction, and systematization of data, comparative analysis of dissertations. Empirical methods are: questionnaire survey, observation, testing, independent peer review, analysis of students’ practical results to determine criteria, indicators and levels of artistic and aesthetic competencies development; pedagogical experiment. Also used is the mathematical statistics method to analyze and determine effectiveness of the technique.